(3HYV aJGhi GdTjN SjOis - (3GdTjN SjOj Hf GdeNJGQ Hf GdeSjHs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje gPG hEfeG eG cJHJ Hg EdjfG CjgG GdeQjO GdQTjO hGdSOjO GdMejO JWdH LhGHg dOjfG bO fXQfG ajg aEPG gh NeS eSGFd Jge hJajO GdeSFhd hGdSGFd GdeSGdI GdChdi ai WdH GdebGUO s
(3BNQgG (B:s
(3aai GdMOjK Cf ef bQC BjI Gd cQSi OHQ cd UdGI cGf GdPi jJhdi bHV QhMg Ph GdLdGd hGdEcQGe hdGjefYg ef ONhd GdLfI ZdG GdehJ hef bQCgG hGdBjJjf HYOgG Zdi bhdg NGdOhf YbH cd UdGI Cef ef hShSI GdTjWGf s
(3fSNI cJHJ HNWhW eNJdaIs
(3cJHJ YfGhjJgG HGdMeQIs
(3hgj YHGQI Yf aJGhi ddeDdas
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJUha hGdBOGH GdTQYjIs